Obesidade infantil : instalação e manutenção, na perspectiva dos pais - Moraes, Priscilla Machado (2011)
This dissertation aims to understand the functioning of families with children affected by obesity in the installation and maintenance of the disease from the perspective of parents. In this circumstance, we considered the feelings expressed by mothers and difficulties facing the obesity of children, strategies used to address the problem in the family context and indicators that could be contributing to the maintenance of the obese children. The work is divided in three articles, one theoretical and two empirical. The first presents a brief history of the human need to feed that showed the changes that led to the proliferation of obesity and, in this scenario, the changes that the family faces in adapting to the environment permeated with so many offers and constant changes, in conjunction with Systemic Theory. The second article identifies the family context under the light of the Systemic Theory, indicators of family dynamics that may be contributing to the installation and maintenance of obesity in childhood. The third article considers elements in the family history of children with obesity, the sentiments expressed by the families and the physical and psychological consequences of disease progression. The research is qualitative in nature, taking into account the experience of participating in the issue. Six mothers were interviewed and a grandmother of children, aged between 8-10 years old, who were in the outpatient clinic of Childhood Obesity Institute of Medicine Professor Fernando Figueira (IMIP) in the city of Recife. We used an interview with previously established questions, and subsequently the results were discussed based on thematic content analysis. The results indicated that all members of the system are involved in the installation of obesity, through the maternal rejection, overprotection offset by food, marital conflicts, and interference from the grandparents in the feeding of grandchildren, which shows confusion in the hierarchy. The difficulties of exchange with the environment showed that families consume of food with high contents of fat, lack of cohesion about food standards and limits are the child elements that may be contributing to the maintenance of childhood obesity